(untitled) (Salud, Arte y Cuidado, 2023)
Empathy has been a term commonly used by society, but it transcends beyond the mere understanding of the other. For Stein, this was a topic of great relevance and made it her research topic for her Doctoral Thesis, entitled “The problem of empathy”. Now, the objective of this article is to reflect on empathy in the training of nursing professionals, since a humanly essential profession in the care of the human being and its teaching is marked by the model acquired in teaching and in the scenarios hospitable. Van Manen’s phenomenological pedagogy is a theory that is easily adapted to this educational level given its humanizing context. The review of both theories allows us to reflect on the teaching practice and its transformation in the area of health sciences.